The Degree of Practice of Academic Department Heads in Yarmouk University of their Role in Managing Meetings and its Relationship to Institutional Excellence from the Faculty Members' Perspective - Salem, Husni; Al-Hamad, Nouwar (Dirasat: Educational Sciences, 2021)
The study aimed to determine the degree of practice of the heads of academic departments at Yarmouk University for their role in the management of meetings and their relationship to institutional excellence, and its sample consisted of (300) members out of (1109), selected by random stratification method, and used two questionnaires to collect data, and descriptive relational survey approach. The results showed that the degree of practice of the heads of academic departments in their role in the management of meetings came (great), and that the level of institutional excellence came (average). The presence of statistically significant differences in the degree of their role in managing meetings is attributed to the variable level of experience in favor of 10 years and less, and to the variable academic rank in favor of assistant professor and associate professor.The presence of statistically significant differences in their estimates of the level of institutional excellence in academic departments due to the variable of experience in favor of 10 years or less, the results did not show any differences due to the variable of academic rank, and showed a statistically significant positive correlation between the degree of practicing their role in managing meetings on the one hand, and the level of institutional excellence in academic departments on the other hand.